The plasma protein profile and cardiovascular risk differ between intima-media thickness of the common carotid artery and the bulb: A meta-analysis and a longitudinal evaluation. (February 2020) - Lind, Lars; Gigante, Bruna; Borne, Yan; Mälarstig, Anders; Sundström, Johan; Ärnlöv, Johan; Ingelsson, Erik; Baldassarre, Damiano; Tremoli, Elena; Veglia, Fabrizio; Hamsten, Anders; Orho-Melander, Marju; et al.
Abstract: Background and aims: Genetic loci associated with CHD show different relationships with intima-media thickness in the common carotid artery (IMT-CCA) and in the bulb (IMT-bulb). We evaluated if IMT-CCA and IMT-bulb differ also with respect to circulating protein profiles and risk of incident atherosclerotic disease. Methods: In three Swedish cohorts (MDC, IMPROVE, PIVUS, total n > 7000), IMT-CCA and IMT-bulb were assessed by ultrasound at baseline, and 86 cardiovascular-related proteins were analyzed. In the PIVUS study only, IMT-CCA and IMT-bulb were investigated in relation to incident atherosclerotic disease over 10 years of follow-up. Results: In a meta-analysis of the analysis performed separately in the cohorts, three proteins, matrix metalloproteinase-12 (MMP-12), hepatocyte growth factor (HGF) and N-terminal pro-B-type natriuretic peptide (NT-proBNP), were associated with IMT-CCA when adjusted for traditional cardiovascular risk factors. Five proteins were associated with IMT-bulb (MMP-12, growth/differentiation factor 15 (GDF-15), osteoprotegerin, growth hormone and renin). Following adjustment for cardiovascular risk factors, IMT-bulb was significantly more closely related to incident stroke or myocardial infarction (total number of cases, 111) than IMT-CCA in the PIVUS study (HR 1.51 for 1 SD, 95%CI 1.21–1.87, p < 0.001 vs HR 1.17, 95%CI 0.93–1.47, p = 0.16). MMP-12 levels were related to this combined end-point (HR 1.30, 95%CI 1.08–1.56, p = 0.0061). Conclusions: Elevated levels of MMP-12 were associated with both IMT-CCA and IMT-bulb, but other proteins were significantly related to IMT in only one of these locations. The finding that IMT-bulb was more closely related to incident atherosclerotic disease than IMT-CCA emphasizes a difference between these measurements of IMT. Graphical abstract: Image 1 Highlights: Intima-media thickness (IMT) in the common carotid artery (CCA) and the bulb was investigated in three cohorts. A meta-analysis showed several proteins in plasma to be differently related to CCA and bulb. IMT-bulb was more closely related to incident atherosclerotic disease than IMT in CCA. These observations suggest a difference between these two measurements of IMT.